2022
DOI: 10.1371/journal.pone.0268133
|View full text |Cite
|
Sign up to set email alerts
|

Corona was scary, lockdown was worse: A mixed-methods study of community perceptions on COVID-19 from urban informal settlements of Mumbai

Abstract: The COVID-19 pandemic has magnified the multiple vulnerabilities of people living in urban informal settlements globally. To bring community voices from such settlements to the center of COVID-19 response strategies, we undertook a study in the urban informal settlements of Dharavi, Mumbai, from September 2020-April 2021. In this study, we have examined the awareness, attitudes, reported practices, and some broader experiences of the community in Dharavi with respect to COVID-19. We have used a mixed-methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…In a study in Dharavi, Mumbai ( n = 450 families), 84.8% households purchased grains from government-subsidized stores under PDS, 58.8% received them for free, 44% received cooked food/rations from ICDS or their employers, and 34% received food from NGOs [ 38 ]. In U.P.…”
Section: Resultsmentioning
confidence: 99%
“…In a study in Dharavi, Mumbai ( n = 450 families), 84.8% households purchased grains from government-subsidized stores under PDS, 58.8% received them for free, 44% received cooked food/rations from ICDS or their employers, and 34% received food from NGOs [ 38 ]. In U.P.…”
Section: Resultsmentioning
confidence: 99%
“…The academic literature on their experiences is also growing (Breman, 2020;Jha, 2020, 2021;Srivastava, 2020a;Hans, Kannabiran, and Mohanty, 2021;Jesline et al, 2021;Raju, Dutta, and Ayeb-Karlsson, 2021;Mathews, De Neve, and Ayeb-Karlsson, 2023). Here we provide empirical evidence of the experiences of non-Keralite migrant workers in Kerala, India, during the first lockdown period of the This adds to a mounting evidence base on these issues across an array of state and regional contexts in India (Carswell, De Neve, and Yuvaraj, 2020;Carswell, De Neve, and Subramanyam, 2022;Ramani et al, 2022).…”
Section: Introductionmentioning
confidence: 87%
“…There is also a high level of trust that exists between SNEHA staff and the community. A study examining community perceptions of COVID-19 from informal settlements in Mumbai found that over 90% of community members trusted information they received from health systems and NGO staff during the pandemic (21). As part of a clusterrandomized control trial, paid women health facilitators were engaged by SNEHA to trigger health behavior change related to maternal and newborn health wherein their role was to create strong community groups and encourage discussion on health issues (22).…”
Section: Inputs ( S) Needed For a Strong Primary Health Carementioning
confidence: 99%